Identificación de los factores que inciden en la baja productividad de la planta purificadora y envasadora de agua softwater. Propuesta implementación de indicadores de producción. - Calderón Paladines, Holger Bolivar (2017)
The present investigation aims the identification of the factors affecting the low productivity in the SOFTWATER plant and the implementation of indicators of production which promote the improvement of the productive efficiency, the study It starts with the analysis of information on the company, staff, working operations and production yields, in order to make a diagnosis of the real situation of the company dedicated to the processing and distribution of bottled water and at the same time mitigate the shortcomings of systems of monitoring, analysis and evaluation of the production process, thus achieving greater assertiveness in decision-making, through quantitative and qualitative approach, using such instruments as the survey, questionnaire and interview. With the result that the main factors affecting productivity are the working force Factor of which were decisive lack of training and staff absenteeism; the same Factor of processes by constant stoppages of production and the capacity Factor for the lack of control in the speed ratings of teams. Indicators are mated and adapted on the ground object of study, which were training, absenteeism, mechanical efficiency and use capacity installed, this allowed to improve efficiently the resources, decrease time loss and resources, as well as errors in production, reduce the excess or defect of inventory and the main thing allowed to increase production lines.